The Role of Risk and Information for International Capital Flows : New Evidence from the SDDS - Hashimoto, Yuko (IMF Working Papers; Working Paper ;, 2012)
In this paper we investigate whether better information about the macroeconomic environment of an economy has a positive impact on its capital inflows, namely portfolio and foreign direct investment (FDI). The purpose of our study is to explicitly quantify information asymmetries by compliance with the IMF's Special Data Dissemination Standard (SDDS). For FDI, we find statistically significant and robust support for this hypothesis: SDDS subscription increased inflows by an economically relevant magnitude of about 60 percent. We also find evidence of aversion against political and macroeconomic risk as determinants of portfolio and FDI flows anduse a non-parametric test for spatial correlation in the residual of capital flows.